An improved method for the identification and cuantitation of polyamines and related compounds as benzoilated derivatives - Hockl, Pablo Francisco (2000)
A simple reversed phase HPLC method was developed for the determination of polyamines (putrescine, cadaverine, spermidine, spermine) and other polycations (n-acetyl putrescine, histamine, n-acetilspermine, agmatine), as their benzoylated derivatives. The advantages of this method,examined in various matrixes (hypothalamus, hypophyses, ovary, and seminal plasma), are its versatility, simplicity, and short time of determination of polyamines and related substances of importance in prokaryotes and eukaryotes, even in different matrixes, using a standard HPLC equipment (UV detection at 254 nm), with good resolution, sensitivity, and reproducibility.